PENGARUH PENDIDIKAN DAN PELATIHAN SERTA MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR PENGAWASAN DAN PELAYANAN BEA CUKAI (KPPBC) TIPE MADYA PABEAN TANJUNG EMAS SEMARANG - Youke Faradhilla Nasution; Hardi Warsono; Hesti Lestari (Journal of Public Policy and Management Review, 2016)
Supervision and Service Office (KPPBC) Type of Customs Madya Tanjung Emas Semarang strive to continue to provide performance and good service in order to implement good governance. In addition to providing education and training, Supervision and Service Office (KPPBC) Type of Customs Madya Tanjung Emas Semarang also strives to motivate employees to improve its performance. The purpose of this study was to determine the effect of education and training as well as the motivation of the employee performance in Supervision and Service Office (KPPBC) Type of Customs Madya Tanjung Emas Semarang. Based on statistical analysis of test results Kendall concordance coefficient W there are significant and positive influence between education and training and motivation on employee performance, evidenced by the value of 0.445 (below 0.50), Which means there is a positive influence between education and training and motivation of the employee performance moves in the same direction. While the coefficient of determination test results indicate that the Education and Training and Motivation affects 19.8% of the performance of employees in the Supervision and Service Office (KPPBC) Type of Customs Madya Tanjung Emas Semarang.